Prevalence and characteristics of late postoperative voiding dysfunction in early-stage cervical cancer patients treated with radical hysterectomy - Kittipat Charoenkwan (2018)
Background: Although effective as a primary treatment for early-stage cervical cancer, radical hysterectomy is associated with significant long-term morbidities, most commonly, voiding dysfunction. Objective: To examine prevalence and characteristics of voiding dysfunction following radical hysterectomy for early-stage cervical cancer. Methods: One hundred-eighty seven patients with FIGO stage IA2-IIA cervical cancer who underwent class II-III radical hysterectomy with systematic pelvic lymphadenectomy between January 1, 2002 and June 31, 2005 were interviewed with questionnaire on voiding function. Medical records were also reviewed for operative and pathologic data. Results: The prevalence of symptomaticbladder dysfunction was 25.1%. There was no statistically significant association between rates of bladder dysfunction and all examined clinical/operative factors. The most common pattern of bladder dysfunction were incomplete emptying in 25 (13.4%) and urgency and nocturia in 21 (11.2%) each. Conclusion: Voiding dysfunction is a common and clinically significant longterm complication following radical hysterectomy. The pattern of dysfunction reflects combined surgical disruption of both parasympathetic and sympathetic innervations of the pelvis.